1997
DOI: 10.1183/09031936.97.10081725
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea syndrome: is the "half-night polysomnography" an adequate method for evaluating sleep profile and respiratory events?

Abstract: Recently, to reduce the costs of polysomnography, split-night studies have been introduced into routine practice: the first part of the night is used to make the diagnosis of obstructive sleep apnoea syndrome (OSAS) and the second part to achieve an appropriate level of continuous positive airway pressure. Since this split-night protocol has not yet been validated by the comparison of polysomnographic pictures obtained in the first and second parts of the night, the aim of this study was to evaluate sleep prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 16 publications
2
17
0
1
Order By: Relevance
“…In 88% of these reproducible patients, optimal effective CPAP levels were reached despite using stricter indicators for CPAP titration and successful CPAP titration as compared to previous reports (7,9,10,(13)(14)(15)(16)(17) (13)(14)(15). If the subject had low AHI during the diagnostic period, the diagnostic part might be expanded into a fullnight protocol, thereby reducing the false-negative diagnostic rate in the split-night protocol.…”
Section: I a T I O N S P L E A S E S E E T H E T E X T Ob L I Qmentioning
confidence: 80%
See 2 more Smart Citations
“…In 88% of these reproducible patients, optimal effective CPAP levels were reached despite using stricter indicators for CPAP titration and successful CPAP titration as compared to previous reports (7,9,10,(13)(14)(15)(16)(17) (13)(14)(15). If the subject had low AHI during the diagnostic period, the diagnostic part might be expanded into a fullnight protocol, thereby reducing the false-negative diagnostic rate in the split-night protocol.…”
Section: I a T I O N S P L E A S E S E E T H E T E X T Ob L I Qmentioning
confidence: 80%
“…In contrast, in most previous reports on split-night study AHI of 5-40 events/h is an indicator for CPAP titration (9,10,(13)(14)(15)(16)(17) and events/ h is an indicator for successful CPAP titration (7,14,15 (15), since the standard duration of diagnostic split-night study has been suggested to be !2 hours, which might leave the remaining sleep time insufficient for CPAP titration (9,10 …”
Section: F I G U R E 1 F L O W-c H a R T O F P A T I E N T S E L E mentioning
confidence: 87%
See 1 more Smart Citation
“…Esta consiste en realizar una PSG estándar en la primera parte de la noche para realizar el diagnóstico, mientras que la segunda parte se establece la presión necesaria de CPAPn para el tratamiento. Algunos autores rechazan el estudio de PSG en noche dividida, argumentando que por el escaso tiempo de registro, la gravedad del SAHOS sería minimizada y que no sería posible titular adecuadamente a los pacientes 18 .…”
unclassified
“…This has the major disadvantage that it halves the time available for introduction of CPAP, perhaps the most critical moment in management. In addition, the first and second halves of the night are not equivalent [19].…”
mentioning
confidence: 99%